Satisfacción de los consumidores en la prestación de servicios financieros por parte de los corresponsales no bancarios del Citibank en el municipio de Floridablanca (Santander) (2017)
In Colombia, exist the image of the Corresponsales no Bancarios (CNB), which is the tool used to satisfy the objective of the financial inclusion policy. This is the case of the population excluded from the financial system, such as the municipality of Floridablanca (Santander) where banks offer their financial services through the CNB, the factors that determine the demand for financial services, the main one is an examination of user satisfaction, asking the Corresponsales No Bancarios? Elaborating a literature review, it identified the main theories that relate the financial development with the economic growth, as well as the importance that the CNBs fulfill in the financial inclusion and through the means of a satisfaction survey, it was concluded that the financial services provided by the banks of Citibank satisfy users in the municipality of Floridablanca (Santander).